ChemInform Abstract: Aptamer‐Integrated DNA Nanostructures for Biosensing, Bioimaging and Cancer Therapy. Issue 25 (June 2016) - Meng, Hong‐Min; Liu, Hui; Kuai, Hailan; Peng, Ruizi; Mo, Liuting; Zhang, Xiao‐Bing
Abstract: Review: 150 refs.